The effects of season-long vitamin D supplementation on collegiate swimmers and divers - Lewis, R. M.; Redzic, M.; Thomas, D. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The purpose of this 6-month randomized, placebo-controlled trial was to determine the effect of season-long (September-March) vitamin D supplementation on changes in vitamin D status, which is measured as 25(OH) D, body composition, inflammation, and frequency of illness and injury. Forty-five male and female athletes were randomized to 4,000 IU vitamin D (n = 23) or placebo (n = 22). Bone turnover markers (NTx and BSAP), 25(OH)D, and inflammatory cytokines (TNF-alpha, IL-6, and IL1-ß) were measured at baseline, midpoint, and endpoint. Body composition was assessed by DXA and injury and illness data were collected. All ath- letes had sufficient 25(OH)D (> 32 ng/ml) at baseline (mean: 57 ng/ml). At midpoint and endpoint, 13% and 16% of the total sample had 25(OH)D < 32 ng/ml, respectively. 25(OH)D was not positively correlated with bone mineral density (BMD) in the total body, proximal dual femur, or lumbar spine. In men, total body (p = .04) and trunk (p = .04) mineral-free lean mass (MFL) were positively correlated with 25(OH)D. In women, right femoral neck BMD (p = .02) was positively correlated with 25(OH)D. 25(OH)D did not correlate with changes in bone turnover markers or inflammatory cytokines. Illness (n = 1) and injury (n = 13) were not related to 25(OH)D; however, 77% of injuries coincided with decreases in 25(OH)D. Our data suggests that 4,000 IU vitamin D supplementation is an inexpensive intervention that effectively increased 25(OH)D, which was positively correlated to bone measures in the proximal dual femur and MFL. Future studies with larger sample sizes and improved supplement compliance are needed to expand our understanding of the effects of vitamin D supplementation in athletes.